Scale to Measure the Attitude of Fish Farmers towards the APART Project in Assam - Saikia, Parag Saikia; Dipak Kumar Sarma; Rituparna Saikia; Pabitra Kumar Saharia; Manashi Hazarika; S M Hussain; Kaustabh Bhagawati; Raktim Sarmah; Dhiren Nath; Madhusmita Deka (Indian Journal of Extension Education, 2024)
A scale was constructed and standardized to measure the attitude of fish farmers towards scientific technologies demonstrated by “Assam Agribusiness and Rural Transformation Project (APART)” from May 2021 to September 2022 in APART-fishery operated districts of Assam using the ‘Scale Product Method’. . Sixty-five (65) experts responded unbiased to the 50 attitude statements related to recommended technologies of fish farming by the project. On the basis of scale values and Q values, only 28 statements were incorporated in the final attitude scale. When administered in a non-sample area, the reliability coefficient of the whole test was 0.90 using Rulon’s formula. Moreover, when the constructed attitude scale was administered among 180 APART beneficiaries during July, 2022 to Sept, 2022, majority i.e. 87.22% of the respondents had most favourable attitude towards technologies demonstrated by APART project which is depicts the impact of the development programme. This attitude scale can be applied practically for measuring the attitude of fish farmers under similar programmes which will aid policy-makers in right decision -making.